Horizontal air-water two-phase slug flow: eulerian and lagrangian data analysis - Chiarello, Conrado (2020)
Multiphase flows are recurrent phenomena both in natural environments – such as volcanic eruptions and blood flow through veins – and industrial environments – such as the nuclear and petroleum industries. Knowledge about the hydrodynamics of the flow as well as its evolution across the pipeline is essential to correctly design pipelines, equipments (such as pumps and slug catchers) and to formulate strategies to optimize the crude oil exploitation from reservoirs. A frequently reported flow pattern in oil pipelines is slug flow, reason why the present study focuses in its investigation. In order to analyze the flow, a novel methodology is proposed and applied to data retrieved in Multiphase Flow Center (NUEM) experimental facilities. The experimental loop has a length of 35.6 m and 26 mm internal diameter and was operated under 18 different slug flow conditions – varying gas superficial velocity from 0.3 to 2.5 m/s and liquid superficial velocity from 0.3 to 3.0 m/s – across 5 different measuring stations composed by a pair of two-wire resistive sensors distributed along the pipe. Data was analyzed using Eulerian reference frame (ERF), which provides distributions for each hydrodynamic parameter in each measuring station for every experimental point, and Lagrangian reference frame (LaRF), which follows unit cells across the pipeline in order to evaluate the change in hydrodynamic parameters of single structures. Correlations were proposed based on retrieved results for hydrodynamic parameters average values and standard deviation. Moreover, a comparison against previous works was made in order to test the presented correlations as well as to propose corrections to the existing ones. Furthermore, details of the flow were investigated using the developed methodology, which was able to provide additional and insightful information about the flow behavior – such as the intrinsically unsteady nature of slug flow, as slug lengths were found to oscillate at all times, even though average values did not report significant changes, which would indicate developed flow conditions. Moreover, it was shown that gas expansion is a driver phenomenon in heavily aerated points, but becomes lees pronounced in low aeration flows – such as plug flows.